Systematic promoter engineering in Lactobacillus casei: Construction and screening of a synthetic aldolase promoter library for enhanced gene expression - Choi, Jun Young; Jang, Jaepyeong; Park, Young Chul; Lee, Pyung Cheon (Process Biochemistry, 2025)
In this study, we engineered a synthetic promoter library for Lactobacillus casei BL23 by randomizing the −35, −10 regions, and spacer sequences of the aldolase promoter. The goal was to generate promoters with varying strengths for use in metabolic engineering applications. Using computational tools (SAPPHIRE and BacPP), we identified core promoter elements and systematically randomized these regions to create 31 variants. Fluorescence-activated cell sorting (FACS) allowed for the isolation of weak, moderate, and strong promoters based on superfolder GFP (sfGFP) expression levels. The strongest promoter exhibited an 8.71-fold increase in sfGFP expression compared to the native aldolase promoter. Sequence analysis revealed specific nucleotide preferences in the core elements, which influenced promoter strength. This study offers a valuable platform for fine-tuning gene expression in L. casei, providing insights for future metabolic engineering applications.
Keywords: Aldolases; Engineering applications; Enhanced gene expression; GFP expression; In silico prediction; In-silico; Lactobacillus casei; Promoter engineering; Promoter strength; Silico prediction; In silico prediction; Lactobacillus casei; Promoter engineering; Promoter strength